Use and perspective of entomopathogenic fungi biocontrol agents of Asian citrus psyllid (Diaphorina citri): A bibliometric review (Research, Society and Development, 2023)
The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), is the main insect vector of the bacteria Candidatus liberibacter spp., which are the causative agents of Citrus Greening disease, also known as Huanglongbing (HLB). The current lack of treatment for the disease means that intensive work is required to manage psyllid populations, mainly through chemical control methods. Since biological control has become a promising management strategy and entomopathogenic fungi are one of the components of integrated pest management, this review aimed to compare previously published results regarding the most efficient fungi for controlling D. citri and to gather information about the best options available. To this end, the bibliography indexed in the Scopus and Web of Science databases was analyzed using bibliometric tools with the R Studio software and the Bibliometrix package. In recent years, Cordyceps fumosorosea, Beauveria bassiana, and Hirsutella citriformis were identified as the most relevant fungus species, showing efficient results. In addition, the countries that publish the most on this subject are also among the largest citrus producers. Studies performed under greenhouse and field conditions are still scarce but necessary to validate the results obtained in the laboratory, as well as those that explore the mechanisms of action involved in the pathogenicity of fungi against D. citri, which are matters to consider in future assessments.